2013
DOI: 10.1002/celc.201300135
|View full text |Cite
|
Sign up to set email alerts
|

Promotion Effects of Sn on the Electrocatalytic Reduction of Nitrate at Rh Nanoparticles

Abstract: We present a comparative study of the activity and selectivity of Rh/C nanoparticles and Sn‐modified Rh/C nanoparticles towards electrocatalytic nitrate reduction in sulfuric acid. Electrochemical techniques, combined with more direct analytical techniques such as mass spectrometry and ion chromatography, were applied to analyse the products obtained during the reaction. Online electrochemical mass spectrometry was employed to detect volatile products, such as nitric oxide (NO), nitrous oxide (N2O) and dinitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 43 publications
(48 reference statements)
0
45
0
Order By: Relevance
“…When both AuPd electrodes are modified with Sn, on both electrodes N 2 O is formed as the dominant volatile product and NH 2 OH as the dominant nonvolatile product. This is similar to the product distribution of the nitrate reduction on the Sn-modified bulk Pd electrode.This product spectrum is similar to the Sn modified platinum [6,24,25], whereas a Sn-modified rhodium electrode produces more ammonia [45], owing to the higher propensity of Rh to break the N-O bond.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When both AuPd electrodes are modified with Sn, on both electrodes N 2 O is formed as the dominant volatile product and NH 2 OH as the dominant nonvolatile product. This is similar to the product distribution of the nitrate reduction on the Sn-modified bulk Pd electrode.This product spectrum is similar to the Sn modified platinum [6,24,25], whereas a Sn-modified rhodium electrode produces more ammonia [45], owing to the higher propensity of Rh to break the N-O bond.…”
Section: Discussionmentioning
confidence: 86%
“…The fragmentation ratio between N 2 O (m/z = 44) and NO (m/z = 30) was found to be 0.202 while between N 2 O and N 2 (m/z = 28) it was 0.0685 [24]. A SEM voltage of 1500 V was used for all species (m/z = 2, 14,15,28,30,31,33,44,45,46). Unfortunately it is not straightforward to deduce quantitative information in terms of faradaic efficiencies for the reaction products from OLEMS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Fundamental studies on nitrate reduction electrocatalysts have focused on noble metal electrodes such as Pt and Pd. 1,3,4 Their catalytic activity has been drastically enhanced by the surface modification with p-block metal adatoms including Sn, [5][6][7][8][9][10][11][12][13] in which the interfaces between the noble metal substrate and the p-block metal adatoms may work as the catalytic active sites. To produce such interfaces, noble metal substrates have been widely used and modified with p-block elements even though the deposition of noble metal nanoparticles on conductive materials containing p-block elements can, in principle, give similar interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the removal of NO is highly sought after and a major challenge for researchers. Extensive progress has been made over Pt 6 7 8 9 10 11 12 , Pd 13 14 15 , Rh 16 17 18 19 20 and Ir 21 22 23 metal surfaces for the catalytic conversion of NO to N 2 . However, the N-O bond dissociation is one of the most important steps and N-O can be dissociated via two pathways (i) direct N-O bond dissociation or (ii) indirect (hydrogenation followed by N-O bond dissociation).…”
mentioning
confidence: 99%
“…However, the N-O bond dissociation is one of the most important steps and N-O can be dissociated via two pathways (i) direct N-O bond dissociation or (ii) indirect (hydrogenation followed by N-O bond dissociation). Earlier studies 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 reported that direct N-O bond dissociation is not thermodynamically favourable over Pt 6 7 8 9 10 11 12 , Pd 13 14 15 , Rh 16 17 18 19 20 and Ir 21 22 23 metal surfaces, but possible from their hydrogenated products (NOH, HNO, HNOH, H 2 NO), which increases the possibility of unwanted by-products. Therefore, the relative selectivity of N 2 vs. other products (N 2 O and NH 3 ) varies from catalyst to catalyst.…”
mentioning
confidence: 99%